PENGENDALIAN SOSIAL PREVENTIF OLEH ORANGTUA PADA ANAK YANG MENGGUNAKAN MEDIA SOSIAL DI DESA SARILABA A - Zulkibli Zulkibli; Sri Buwono; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe title of this study is "Preventive Social Control Analysis by Parents in Children Using Social Media in Sarilaba A Village, South Jawai, Sambas District ". The problem in this research is, how to prevent social control by parents in children who use social media in Sarilaba A Village, namely by providing guidance, direction and appeal to children who use social media. This study aims to determine preventive social control by parents in children who use social media in Sarilaba A Village. The method used is a qualitative method with descriptive analysis. Data collection techniques using observation, interviews and documentation. The results showed that parents have carried out preventive social control to their children by providing guidance, parents have advised and self-understanding to children about the limitations of using social media so that children do not imitate negative examples of social media. Then briefing, parents have given guidance to children regarding the use of time so that the child's free time is used on positive things such as studying, doing schoolwork and helping with homework. As well as appeal, parents have asked and instructed subtly, without any compulsion and the child's awareness to follow the appeal of his parents.Keyword: Social Control, Preventive, Social Media.